Pediatric patients with disabilities - assessment of satisfaction with anesthesia - Schiff, Jan-Henrik; Ihringer, Katja; Martin, Eike (Pediatric anesthesia, 2012)
Background: Opinions about satisfaction with care are rarely obtained from disabled children and their carers, and few studies of this type exist in the area of pediatric anesthesia. We specifically aimed to assess groups of children with disabilities and Down syndrome and aimed to identify factors influencing satisfaction in these groups. Methods: We assessed two groups of children using the Paediatric Perianesthesia Questionnaire (PPQ). Families with Down syndrome children (Down syndrome group, DSG) were approached via a Down syndrome family support magazine, and families with disabled children were enrolled in hospitals. Two hundred and fifteen disabled children (125 from the journal, 90 from the hospitals) were compared to matching controls without disabilities. Controls were drawn randomly using computer-generated tables of random numbers using data from the PPQ validation, to match cases for confounding variables. Results: Satisfaction was lower in both groups with disabilities (P < 0.05) (lowest in the DSG), fewer would choose the hospital or anesthetic department again. In both of the disabled groups, negative comments were related to the anesthetists’ behavior during the consultation, the content of the consultation, and how anxiety was dealt with. Ninety five percent in the DSG reported that the anesthetist had not mentioned or enquired about atlantoaxial instability. Satisfaction was lower than the rest of the respective group if memories of the disclosure of the disabling condition were negative (P = 0.006) or if potential offensive terms had been used during the consultation (P < 0.001). Conclusions: This is the first study to assess families with disabled children for satisfaction with anesthesia. Our findings suggest that parents of children with disabilities are less satisfied with their anesthetic care than parents of children without disabilities. Potential bias comes from the self-selection of the DSG and the recall period in this group.
Gesehen am 04.05.2018